2012
DOI: 10.4100/jhse.2012.7.proc1.15
|View full text |Cite
|
Sign up to set email alerts
|

Diet-Induced Thermogenesis: Comparison of Two Isocaloric Meal-Replacement Shakes. A pilot study

Abstract: Kumstát M, Hrazdira L. Diet-Induced Thermogenesis: Comparison of Two Isocaloric Meal-Replacement Shakes. A pilot study. J. Hum. Sport Exerc. Vol. 7, No. Proc1, pp. S140-S146, 2012. The aim of this study is to evaluate the differences in diet-induced thermogenesis (DIT) between two liquid meal-replacement shakes of different macronutrient compositions: high protein (HP) and high carbohydrate (HC) meal. Five male subjects (26 ± 3.7 y, body mass index 24.6 ± 1.7 kg·m -2 ) completed the crossover, single-blind stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Wingfield et al [ 20 ] reported that an acute protein feeding resulted in significant elevations in resting energy expenditure for 60 min following exercise compared to a pre-exercise carbohydrate feeding. Such conclusions are supported by a well-developed body of research reporting that the consumption of high protein meals or short-term high protein diets results in elevated rates of postprandial dietary thermogenesis compared to lower-protein controls [ 24 , 32 35 ]. Interestingly, a recent report has suggested that moderate intensity exercise may potentiate dietary thermogenesis.…”
Section: Discussionmentioning
confidence: 88%
“…Wingfield et al [ 20 ] reported that an acute protein feeding resulted in significant elevations in resting energy expenditure for 60 min following exercise compared to a pre-exercise carbohydrate feeding. Such conclusions are supported by a well-developed body of research reporting that the consumption of high protein meals or short-term high protein diets results in elevated rates of postprandial dietary thermogenesis compared to lower-protein controls [ 24 , 32 35 ]. Interestingly, a recent report has suggested that moderate intensity exercise may potentiate dietary thermogenesis.…”
Section: Discussionmentioning
confidence: 88%